Millennia of legal content criteria of lies and truths: wisdom or common-sense folly? - Sporer, Siegfried L.; Masip, Jaume (Frontiers in Psychology, 2023)
Long before experimental psychology, religious writers, orators, and playwrights described examples of lie detection based on the verbal content of statements. Legal scholars collected evidence from individual cases and systematized them as "rules of evidence" (e.g., Mittermaier, 1834). Some of these resemble content cues used in contemporary research, while others point to working hypotheses worth exploring. To examine their potential validity, we re-analyzed data from a quasi-experimental study of 95 perjury cases. The outcomes support the fruitfulness of this approach. Travelling back in time searching for testable ideas about content cues to truth and deception may be worthwhile.